2015
DOI: 10.5430/ijba.v6n2p96
|View full text |Cite
|
Sign up to set email alerts
|

The Practice of Knowledge Management in Private Higher Education Institutions in Egypt: The Demographics Effect

Abstract: Managing knowledge in higher education institutions is under scrutinizing due to the mismatch between the demands of the labor market and the education output. Knowledge management research focuses on the technical aspect rather than the humane one which includes the employees who directly interact with the system. The aim of this paper is to analyze the interaction of age and gender of Egyptian academicians, and its effect, on Knowledge Management. Data was gathered using questionnaire in which 73 academician… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Even others also accept their credibility as a 'giver' of knowledge. Many studies have been conducted focussing on the demographic variables and knowledge Management (Damghanian, et [21] found that women of younger age (20-35 years) showed active knowledge sharing behaviour. In the meantime studies by Mogotsi (2009) [22] showed that there is no significant relationship between age and knowledge sharing behaviour.…”
Section: Age and Knowledge Sharingmentioning
confidence: 99%
“…Even others also accept their credibility as a 'giver' of knowledge. Many studies have been conducted focussing on the demographic variables and knowledge Management (Damghanian, et [21] found that women of younger age (20-35 years) showed active knowledge sharing behaviour. In the meantime studies by Mogotsi (2009) [22] showed that there is no significant relationship between age and knowledge sharing behaviour.…”
Section: Age and Knowledge Sharingmentioning
confidence: 99%
“…A main concern of KM is to exploit the tacit knowledge and make it available as well for others to employ it (King, 2009). Noticeably, the 1990's marked the starting growing attention to KM from both the academic and management levels (El Badawy, 2015). According to (Groff, 2012), KM can be defined as the systematic process inside the organization for capturing, structuring, managing and disseminating knowledge for efficient work.…”
Section: Knowledge Management: Perspectives and Significancementioning
confidence: 99%
“…Accordingly, a culture of knowledge sharing should be established. Then, empowering employees and setting the appropriate work design are crucial to motivate employees for creating knowledge as well as to encourage the efficient communication and dissemination of knowledge inside the organization (Wang 2012;El Badawy 2015). Successful organizations should clearly set KM systems to promote effectively creation, storage, and sharing of knowledge to maintain their competitiveness.…”
Section: Knowledge Management: Human Resource Management (Hrm) As a Kmentioning
confidence: 99%
“…However, Ismail and Yusof (2009) reported that there was no correlation between demographic variables and knowledge sharing behavior based on a study in a Malaysian ministry. Badawy and Magdy (2015) reviewed the influence of demographic characteristics on employees' attitudes toward knowledge sharing, with a focus on age and gender. They reported that women are more successful in obtaining and transferring knowledge.…”
Section: Demographic Characteristics and Knowledge-sharing Culturementioning
confidence: 99%
“…They further suggested that the interaction of age and gender shows that women of the younger generation (20-35 years) are more active in knowledge sharing. However, Badawy and Magdy (2015), based on studies conducted by Darvish, Ahmadnia, and Qryshan (2013) and Hasnain (2013), concluded that there were no statistical differences between men and women in their knowledge management activities, including knowledge sharing. In their view, the effect of gender and age on knowledge sharing remained inconclusive and unsubstantiated.…”
Section: Demographic Characteristics and Knowledge-sharing Culturementioning
confidence: 99%